Role of Insect Pests in Minapadi Systems as Natural Feed for Catfish and Their Impact on Pest Control - Tien Aminatun; Budiwati; Suhartini; Rizka Apriani Putri; Arsyad Sujangka; Fardan Yusuf Ibrahim; Hasna Kamila Hanum; Genius Abid Karunia; Syfa Trinandita (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2026)
Minapadi is a term for the integrated cultivation of rice and fish. This study aimed to: (1) determine the potential of insect pests from the rice field ecosystem as a natural feed source for catfish in a Minapadi system; and (2) analyze the system's effectiveness in naturally controlling insect pest populations in rice. Three experimental plots were established: Plot A combined a rice field with acatfish pond equipped with a light trap; Plot B combined a rice field with a catfish pond without a light trap; and Plot C was a rice field alone, serving as a control. The methodology encompassed land preparation and plot layout, maintenance of rice and catfish, insect sampling, measurement of rice plant growth parameters, assessment of catfish weight and protein content, and statistical data analysis. The potential of insects as feed was indicated by the significant abundance of captured insects, categorized as either pests or natural enemies. Insect abundance across all plots increased weekly during observations. The insect pest diversity index was moderate in the integrated plots (A and B) and low in the control plot (C). The diversity index for natural enemies was moderate acrossall three plots. Statistical analysis revealed that the variation in insect pest abundance and diversity did not significantly influence the protein content levels measured in the catfish. Over all, Minapadi framework demonstrates promise as a component of integrated pest management however supplemental strategies such as light traps may be necessary to enhance control of specific pestpopulations.